1986 y-Walk participants signing in - Unknown:::Creator::::::::::::
Negative shows men and women who are participants in the 1986 y-Walk. They are signing in at tables or milling around the YWCA building which is in the background. There are balloons at the tables and signs that indicate an alphabetical organizational method to signing in. The readable signs say: "Holcomb. Janigian" and Martin. McManis." Some of the participants are wearing tee shirts that read: "Walk for women. YWCA 1986."